UJI BEBERAPA TRICHO-KOMPOS TERFORMULASI TERHADAP PERTUMBUHAN DAN PRODUKSI CABAI MERAH - Rizki, Hanny Bie; Puspita, Fifi; ', Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to determine the influence some of the Tricho-compost formulated and to get the best Tricho-compost formulated in improving the growth and yield of red chilli. The research was conducted at the technical implementation unit Faculty of Agriculture University of Riau. The research was performed in six months, from June 2014 until November 2014. This research was performed experimentally using a Complete Randomized Design (CRD) consisting of 5 treatments and four replicates. The analysis of variance was use for data and Duncan's New Multiple Range Test (DNMRT) at the 5% level was used for mean separation. The observation is performed on each unit of the experiment with two examples of plants. As for the parameters observed in this study is dichotomous height, plant height, stem diameter, canopy width, flowering date, harvesting date, fruit length, fruit diameter, weight per fruit and weight of fruit per plant. The results showed those the treatment of Tricho-compost formulated, increased stem diameter, canopy width, flowering date, harvesting date, fruit length, fruit diameter, weight per fruit and weight of fruit per plant more than non treatment with the exception for dichotomous height and plant height. Treatment of Tricho-compost formulated (TKKS) show the best results by increasing 25,88% stem diameter, 8,16% flowering date, 68,96% fruit diameter, 47,95% weight per fruit and 74,26% weight of fruit per plant more than treatment of some Tricho-compost formulated. Keywords : Tricho-compost, growth, yield, red chilli